THE INFLUENCE OF SUPPORTING FACILITIES, THE QUALITY OF HEALTH CENTER SERVICES, AND THE MEDICAL PERSONNEL COMPETENCYON PATIENT LOYALTY WITH SATISFACTION AS AN INTERVENING - Yayak Hendarini; Riyanto Setiawan; Toni Herlambang (Universitas Muhammadiyah Bengkulu, 2026)
Quality health services are a crucial factor in enhancing patient satisfaction and loyalty, particularly in primary healthcare facilities such as health centers. However, numerous challenges remain regarding supporting facilities, service quality, and the competence of medical personnel, all of which need to be optimized to meet patient expectations. This study aims to analyze the influence of supporting facilities, service quality, and medical personnel competence on patient loyalty, both directly and indirectly through patient satisfaction as a mediating variable. Data were collected from patients who utilized services at the Jember Regency Health Center using a survey method and analyzed with Structural Equation Modeling (SEM) via WarpPLS software. The results indicate that supporting facilities, service quality, and medical personnel competence have a positive and significant direct effect on patient loyalty. Additionally, these three variables positively and significantly impact patient satisfaction, which in turn mediates their influence on patient loyalty. These findings underscore the importance of enhancing comfortable facilities, high-quality services, and professional medical personnel competencies to boost patient satisfaction and loyalty in primary healthcare services. This research is expected to serve as a reference for Community Health Center management in developing strategies to improve service quality and maintain patient loyalty